PREVALENCE OF VAGINAL CANDIDIASIS AMONG PREGNANT WOMEN ATTENDING ANTENATAL CARE IN DOMA HOSPITAL, GOMBE, NIGERIA - MANSUR, A; IBRAHIM, H.I; SULEIMAN, M.A; HAJARA. L.S; FATIMA, U.M; NURU, A.G; MENEGBE, N.Z (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Pregnant women commonly develop increased vaginal discharge which may lead to pregnancy complications like abortions, premature birth, low birth weight and other morbidities. This study was aimed to determine the occurrence of vaginal candidiasis among pregnant women attending antenatal care in Doma Hospital Gombe, Nigeria. A total of fifty (50) pregnant women were examined. Samples of high vaginal swabs were collected from each patient and tested by microscopic examination then cultured on Sabouraud Dextrose agar [SDA]. Colonial morphology, wet preparation, gram staining, germ tube test, were carried out for identification of the isolated organisms. From the total fifty (50) samples collected and examined for candida, thirty-eight (38) (76%) showed positive while twelve (12) (24%) showed negative. The isolates obtained were related to number of pregnancy (gravidae), 25(65.5%) were multi-gravidae while 13(25.5%) were primigravidae. The result of this study revealed that pregnant women in the second trimester of pregnancy had the highest incidence of candidiasis 20(52.5%), followed by third trimester 12(31.5%) while the least 6(16%) was obtained in first trimester. Furthermore, age between 21-25 years had highest occurrence of Candida albicans 15(39.5%), followed by age between 26-30 years 10(26.5%), age 31-35 had 7(18.5%) where age between 16-20 years had the least occurrence 6(15.5%).The results of this study revealed a high occurrence of vaginal candidiasis among pregnant women and this may be due to contributing factors poor personal hygiene during pregnancy, poor dietary habit, wearing of tight-fitting synthetic underclothing, shortage of effective treatment, high sexual activities during pregnancy, change in pH of the vagina